2020
DOI: 10.3390/ijerph17186833
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Obesity-Related Anthropometric Factors on Cardiovascular Risks of Homeless Adults in Taiwan

Abstract: Homelessness is a pre-existing phenomenon in society and an important public health issue that national policy strives to solve. Cardiovascular disease (CVD) is an important health problem of the homeless. This cross-sectional study explored the effects of four obesity-related anthropometric factors—body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR)—on cardiovascular disease risks (expressed by three CVD markers: hypertension, hyperglycemia, and hyperlip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The authors observed that the prevalence of hyperglycemia, hypertension, and hyperlipidemia in the examined patients was significantly higher than in the general population and that the obesity-related indicators, including BMI, were all risk factors for hypertension and hyperlipidemia. Furthermore, a history of myocardial infarction was shown to be more common in participants with higher BMIs; no such link was detected for strokes [49]. In contrast, Yamamoto et al [50] found that the mean BMI and blood pressure in participants living in temporary residences were similar to those of the general population and confirmed the presence of significant correlations between hypertension, liver dysfunction, and dyslipidemia and the duration of both homelessness and residence status.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors observed that the prevalence of hyperglycemia, hypertension, and hyperlipidemia in the examined patients was significantly higher than in the general population and that the obesity-related indicators, including BMI, were all risk factors for hypertension and hyperlipidemia. Furthermore, a history of myocardial infarction was shown to be more common in participants with higher BMIs; no such link was detected for strokes [49]. In contrast, Yamamoto et al [50] found that the mean BMI and blood pressure in participants living in temporary residences were similar to those of the general population and confirmed the presence of significant correlations between hypertension, liver dysfunction, and dyslipidemia and the duration of both homelessness and residence status.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of metabolic diseases and associated pathologies, 40 patients reported suffering from CVD, 15 suffered from diabetes, 42 were overweight, and 36 were obese. Research conducted on 297 homeless adults in Taipei City analyzed the participants' obesity-related markers and identified patients at risk of CVD [49]. The authors observed that the prevalence of hyperglycemia, hypertension, and hyperlipidemia in the examined patients was significantly higher than in the general population and that the obesity-related indicators, including BMI, were all risk factors for hypertension and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] The data based on sources from Japan and Taiwan presents European level of obesity frequency. 50,51…”
Section: Duration Of Lifementioning
confidence: 99%